Photodynamic Therapy: Boron Dipyrromethene Nano‐Photosensitizers for Anticancer Phototherapies (Small 32/2019). Issue 32 (9th August 2019) - Sun, Wen; Zhao, Xueze; Fan, Jiangli; Du, Jianjun; Peng, Xiaojun
Abstract : In article number1804927, Jiangli Fan and co‐workers comprehensively survey the recent development of boron dipyrromethene nanophotosensitizers for cancer treatment via photodynamic therapy (PDT), photothermal therapy (PTT), and the combination of PDT and PTT. Their detailed applications in vitro and in vivo are discussed, and their potential for new tumor phototherapies are highlighted.